Economics / Second Edition - Parkin Michael (Academic Press, Inc, 1993)
Introduction, How Market Works, Household's Choices, Firms' Choices, Markets for Good and Services, Markets for Factors of Production, Markets and Uncertainty and Distribution, Markets and Government, Introduction to Macroeconomics, Aggregate Demand Fluctuations, Aggregate Supply and Inflation and Recession, Macroeconomic Policy, International Economics, Growth and Development and Reform, Index.